(untitled) (Research, Society and Development, 2021)
In the chemical composition of beer, phenolic compounds that contribute to the sensory characteristics and show antioxidant capacity are found and help to maintain oxidative stability. The compilation of 35 studies, published between 2006 and 2020, aimed to gather information about the phenolic compounds and the antioxidant activity of beers and to relate the results obtained with the types of beers analyzed. The results showed that both, the content and the profile of phenolic compounds and the antioxidant activity of beer, are influenced by the ingredients used and by the manufacturing process. Ale beers, dark in color, with higher bitterness and alcohol content, showed higher values of phenolic compounds and antioxidant activity than other types and styles. Analyzes for specialty beers showed that the addition of diversified foods contributed to improving the bioactive composition of the beverage. Over 50 phenolic compounds have already been identified in beers, derived from the ingredients used in the manufacture. Among the most frequent phenolic compounds are phenolic acids, such as ferulic and caffeic acids and catechins. A close correlation between the content of total phenolic compounds and the antioxidant capacity was observed, and the presence of some specific compounds may increase this activity. However, during beer storage, a decrease in antioxidant activity may occur due to changes in the structures of molecules related to this capacity. These studies contribute to the improvement and development of beverages with a higher content of phenolic compounds, improving their oxidative stability and shelf life.